Subjects of public authority in matters of combating terrorism: legal regulation, administrative and criminal aspect - Sinkevych, Olena; Komissarova, Natalia; Tkachenko, Oleksandr; Leheza, Yevhen; YurovskÐ°, Viktoriia (Universidad Hemisferios, 2024)
The purpose of the research is disclosing the administrative and legal status of public administration subjects regarding countering terrorism. Main content. It has been established that a fairly clear and logical structure of state bodies regarding organization and coordination of the fight against terrorism has been created in Ukraine. The system of counter-terrorism entities is a set of specific, legally defined entities that interact with the goal of preventing, detecting, stopping, and minimizing consequences of terrorist activities. Methodology: The following methods were used in the research: analysis of biographical sources, synthesis, deduction, comparative analysis, meta-analysis, etc. Conclusions. It has been established that the President of Ukraine, the Verkhovna Rada of Ukraine and the Cabinet of Ministers of Ukraine are the key actors in countering terrorism in Ukraine in the system of higher authorities. The defining areas of activity of the President of Ukraine in the sphere of countering terrorism are the activities aimed at the regulatory and legal support of countering terrorism in Ukraine creation, liquidation, reorganization and management of the relevant counter-terrorism subjects.